2023
DOI: 10.3390/f14071339
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Awareness, Policy Perception, and Green Production Behaviors of Farmers Living in or near Protected Areas

Abstract: Research highlights: Ecological policies must balance ecosystem protection by promoting the sustainable livelihoods of farmers living in or near protected areas; however, the intrinsic motivations of farmers to adopt green production behaviors (GPBs) are poorly understood. Background and objectives: We explored how ecological policies affect the GPBs of farmers in agroforestry. Materials and methods: We conducted questionnaires of farmers in 11 counties of Sichuan Province, China, with abundant protected areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Te study also revealed that 32.2% of the farmers had access to tree conservation training, whereas 67.8% did not. Tis suggests the need for training initiatives for farmers [34]. Most farmers in the study area had land certifcation (92.2%), indicating secure tenure and willingness to adopt long-term agricultural practices such as agroforestry, despite a small portion lacking legal recognition [53].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Te study also revealed that 32.2% of the farmers had access to tree conservation training, whereas 67.8% did not. Tis suggests the need for training initiatives for farmers [34]. Most farmers in the study area had land certifcation (92.2%), indicating secure tenure and willingness to adopt long-term agricultural practices such as agroforestry, despite a small portion lacking legal recognition [53].…”
Section: Discussionmentioning
confidence: 93%
“…Te study revealed that most farmers in the study area were illiterate, with only a quarter being literate. Tis low level of education afects their understanding of agroforestry concepts and associated benefts, suggesting the need for education and training programs [34]. Most farmers (55.6%) had access to electronic media, including radio, which showed that they could efectively disseminate information about agroforestry practices and their benefts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The report to the 20th National Congress Agriculture 2024, 14, 680 2 of 17 of the Communist Party of China emphasized that China should continue to promote green development, promote the harmonious coexistence between humans and nature, and accelerate green transformation. Therefore, it is necessary for farmers to adopt green production [8,9]. Existing research indicates that farmers exhibit limited enthusiasm and low adoption rates for green production technologies [10].…”
Section: Introductionmentioning
confidence: 99%